The respiratory virome in chronic obstructive pulmonary disease. (July 2018) - Garcia-Nuñez, Marian; Gallego, Miguel; Monton, Concepción; Capilla, Silvia; Millares, Laura; Pomares, Xavier; Espasa, Mateu; Ferrari, Rafaella; Moya, Andres; Monsó, Eduard; Perez-Brocal, Vicente
Aim: To characterize the respiratory virome in moderate/severe chronic obstructive pulmonary disease (COPD) patients using metagenomics, with healthy subjects as the reference.Patients & Methods: Sputum COPD samples were collected during stability and exacerbations with negative usual-care microbiologic analysis.Results: Eukaryotic viruses from the Anelloviridae, Herpesviridae and Retroviridae families and phages from the Shiphoviridae family were commonly found in COPD, and the respiratory virome in stability and noninfectious exacerbations showed a substantial similarity. DNA viruses with the highest relative abundance in COPD are Anelloviridae.Conclusion: These results support a colonizing role for eukaryotic viruses in COPD and highlight the importance of analyzing both DNA and RNA viruses when focusing on the respiratory virome.